Mono‐6A‐(4‐methoxybutylamino)‐6A‐β‐cyclodextrin as a chiral selector for enantiomeric separation. Issue 15 (5th June 2014) - Wang, Shuye; Wang, Yiying; Zhou, Jie; Lu, Yingying; Tang, Jian; Tang, Weihua
<x xml:space="preserve">Abstract</x> A new member of the family of methoxylalkylamino monosubstituted β‐cyclodextrins, mono‐6A‐(4‐methoxybutylamino)‐6A‐β‐cyclodextrin, has been developed as a chiral selector for enantioseparation in capillary electrophoresis. This amino cyclodextrin exhibited good enantioselectivities for 16 model acidic racemates including three dansyl amino acids at an optimum pH of 6.0. Excellent chiral resolutions over six were obtained for α‐hydroxy acids and 2‐phenoxypropionic acids with 3.0 mM chiral selector. The good chiral recognition for α‐hydroxyl acids was attributed to inclusion complexation, electrostatic interactions, and hydrogen bonding. The hydrogen‐bonding‐enhanced chiral recognition was revealed by NMR spectroscopy. The chiral separation of acidic racemates was further improved with the addition of methanol (≤10 vol%) as an organic additive.